Anesthetic Management of a Brown Bear (Ursus arctos) Captive Undergoing Incisional Biopsy of a Skin Nodule - Vieira Nunes, Marllos Henrique; Duarte Pacheco, Acácio; Alfenas Duarte, Matheus; Rodrigues, Marcelo Campos; Mendonça Castro, Fernanda De Cássia; Rodrigues dos Santos, Thays Garreto; Wagatsuma, Juliana Tessália (Acta Scientiae Veterinariae, 2021)
Background: The brown bear (Ursus arctos) is considered one of the largest terrestrial carnivores, native from temperate forest regions of North America, Europe and Asia. In Brazil, they are founded in captivity and their safe capture and immobilization are obtained with one effective anesthesia for management and surgical and diagnostic procedures. Some anesthetic protocols are described for these purposes, however, there is a lack for data on the anesthetic and adverse effects they have on bears when used. The aim of this case is to report the use and effects of the association of dexmedetomidine with tiletamine and zolazepam in the chemical containment of a captive adult brown bear. Case: A 33-year-old female brown bear, weighing 100 kg, belonging to the Zoobotanic Park of Teresina, Piauí, Brazil, was chemically immobilized for an incisional biopsy of a cutaneous nodule with 1.0 cm diameter in the right face region. The anesthetic protocol included 6 μg/kg of dexmedetomidine associated with 3 mg/kg of tiletamine and zolazepam, administered intramuscularly by dart into the gluteal region of the right pelvic limb. The animal showed moderate ataxia at 5 min and assumed sternal decubitus 7 min after anesthetic administration. The bear’s degree of sedation was considered adequate and safe to perform the biopsy at 10 min after administration. Heart rate (47 ± 3 bpm), respiratory rate (17 ± 2 mpm) and rectal temperature (38.7 ± 0.1ºC) were monitored. The bear remained immobile and unconscious throughout the procedure, with intense muscle relaxation, bilateral eyeball rotation, absent lateral palpebral reflex and mild medial reflex and without nystagmus. Complementary sedative doses were not necessary. At the beginning of anesthetic recovery, the bear received 6 µg/kg of atipamezole, intramuscularly. After 25 min of administration of atipamezole, the animal showed signs of recovery in the level of consciousness and reactivity to external stimuli, and assumed the quadrupedal position at 60 min after reverser application. Discussion: Even in captivity, the bears behavior is unpredictable and attack can occur, causing trauma or death to people. For this, the chemical immobilization is important to keep safety of everyone. This procedure was performed using blowgun-assisted darts thrown by a staff member who had experience in using this method, who darted accurately and effectively. The latency time observed after administration of the anesthetic protocol used is similar to reported in other studies with bears that also received intramuscular dexmedetomidine and tiletamine and zolazepam and showed intense muscle relaxation and immobility. The doses used contributed to the absence of bradycardia and hypoventilation and, performing the procedure in the morning, when the temperature is milder in the city, minimized the chance of hyperthermia and thermal stress in the animal, not requiring body cooling. The use of dexmedetomidine in chemical containment protocols for short and minimally invasive procedures allows the subsequent use of its antagonist, atipamezole, contributing to a shorter recovery time, return of the animal’s degree of consciousness and lower incidence of ataxia after assuming a quadrupedal position. The anesthetic protocol used was considered efficient, providing a quick and gentle chemical containment, adequate anesthetic plan and good anesthetic recovery in an adult brown bear from captivity. Keywords:atipamezole, dexmedetomidine, wildlife. Título: Manejo anestésico de um urso pardo (Ursus arctos) cativo submetido a biópsia incisional de nódulo cutâneo Descritores: atipamezole, dexmedetomidine, animais selvagens.